Analisis Pelanggaran Etika Bisnis Terhadap Penayangan Iklan Rokok Di Pertelevisian Indonesia - Sura Klaudia; Kirei Hoshi Fatayo Widyawati; Ellyn Citra Putranti (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2021)
No single business actor does not advertise their products, be it products made from herbal ingredients, synthetic materials, or even hazardous materials. Advertising itself can be done in various ways, and one way that is currently immensely loved by business people is to advertise their products through television media. Cigarette advertising itself has been considered to have committed several business ethics violations. The purpose of this study was to determine whether there were violations of business ethics that occurred during the broadcast of cigarette advertisements on television. The type of research that will be applied in this research is qualitative research using descriptive qualitative methods. The results showed two kinds of business ethics violations that occurred during the broadcast of cigarette advertisements; the two types of violations were moral violations and empathy violations. Moral violations occur because of the ineffectiveness of limiting cigarette advertisements that the government has set. Meanwhile, the violation of empathy occurs because of a sense of indifference to the cigarette company about the harmful effects that can be caused by smoking behavior on consumer health.